2019
DOI: 10.1111/jan.14000
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of randomized controlled trials of laughter and humour interventions on depression, anxiety and sleep quality in adults

Abstract: Aim To quantify the effect of laughter and humour interventions on depression, anxiety, and sleep quality in adults. Design A meta‐analysis of randomized controlled trials. Data Sources PubMed, Embase, PsycINFO, Web of Science, Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure, Weipu, and Wanfang Data were searched from their inception up to December 2018. Review methods The reporting of this meta‐analytical review was conducted according to the guidelines of the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 51 publications
5
57
0
1
Order By: Relevance
“…Similarly, there are studies reporting that laughter yoga significantly reduced individuals' anxiety and depression levels (Kim et al, 2015; Yazdani et al, 2014; Yu & Kim, 2009). Zhao et al's (2019) meta‐analysis study stated that laughter yoga significantly reduced depression and anxiety. The results of most of the above studies have shown that laughter yoga provides a significant reduction in anxiety and depression levels, which is supportive of the results obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are studies reporting that laughter yoga significantly reduced individuals' anxiety and depression levels (Kim et al, 2015; Yazdani et al, 2014; Yu & Kim, 2009). Zhao et al's (2019) meta‐analysis study stated that laughter yoga significantly reduced depression and anxiety. The results of most of the above studies have shown that laughter yoga provides a significant reduction in anxiety and depression levels, which is supportive of the results obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the impact of humour, it contributes to psychosocial and physical health in older adults. Some studies (Ganz, & Jacobs, 2014; Low et al, 2014; Houston et al, 1998; Zhao et al, 2019) have shown that it can effectively relieve negative emotions, such as anxiety and depression in older adults. Physiologically, humour may relieve stress by decreasing physical tension (Fry & Salameh, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Through the implementation of a laughter program, the author found an improvement in depressive symptoms. According to Zhao et al (2019), laughter and humor interventions are effective in reliving depression, anxiety and improving sleep quality in adults. Laughter simulated program improves the quality of social interaction, physical limitations, symptoms of CKD (decreased appetite, pain and shortness of breath), and has positive effects on mental health.…”
Section: Benefits Of Laughter-inducing and Humor Nursing Interventions In Depression Decrease And Control Of Stress And Anxietymentioning
confidence: 99%